Crossing course and degree boundaries in developing an immersive MOOC experience - Kamalludeen, Rosemaliza; Nordin, Mohd. Shukri (Centre for Global Open Access Learning - Immersive Technology & Quality Assurance (GOAL-ITQAN), Universiti Sains Islam Malaysia (USIM), 2017)
Highlights: This is a collaborative teaching project by two instructional technologists in delivering four different courses of different levels at the Kulliyyah of Education, IIUM. Students of the four different courses collaborated to develop a Massive Open Online Course (MOOC) on the OpenLearning platform as part of the course completion requirement. Each course plays unique roles in the project based on the individual course learning objectives.